ANALYSIS OF RESIDUAL STRESS BY X-RAY DIFFRACTION AND STUDY OF MICROSTRUCTURE IN WELDED JOINT OF ASTM A-36 MARINE STEEL - Souza, M. C. L.; Magalhães, I. P.; Silveira de Sá, G. M.; Monine, V. I.; Perez, R. S.; Tapanes, N. C. O. (Revista de Engenharia Térmica, 2023)
ASTM A-36 marine steel is one of the most used and classified as a medium strength carbon steel. Its characteristics and purpose are in common applications and in metallic structures in general, sawmills, walkways, agricultural machinery and implements, road, rail and oil implements. It is used in angles, round, flat and square bars and I, U and T profiles. In this work, 10 mm sheets, with a V chamfer, were welded using the MIG/MAG process and X-Ray Diffraction measurements were carried out to study of residual stresses caused by the welding process. Then samples were taken for metallography and microscopy in the Scanning Electron Microscope (SEM). They were also performed in the three regions of the weld: base metal (MB); thermally affected zone (ZTA) and in the molten zone (ZF) Brinell hardness tests, to determine the energy stored in the regions of the weld bead. Vickers Microhardness measurements were also made at the ZTA, as it is a very narrow range, to give more precision to the hardness measurements. The X-Ray Diffraction test showed that the air-cooled samples are compressive and the water-cooled samples are tensile. The micrographs of the samples, in the region of the weld, showed that the ferritic phase prevailed in the molten zone. It was also observed the precipitation of carbides and alloying elements, in addition to the presence of martensite. It is concluded, therefore, that the results for the MIG/MAG welding were satisfactory and recommended for the welding of ASTM A-36 Steel.